ATYPICAL GUILLAIN-BARRé IN THREE MONTHS IN SOUTH EAST WALES. Issue 12 (15th November 2016) - Arms-Williams, Bradley; Woodward, Chris; Thomas, Rhys; Payne, Gareth; Thomas, Benny; Johnston, Janet Ann; Pickersgill, Trevor
Abstract : Introduction: We report a cluster of five cases of atypical Guillain-Barré syndrome (GBS) from South East Wales admitted between October and December 2015. Methods: Each patient was examined, case notes were scrutinised and nerve conduction studies were performed. Each had a cerebrospinal fluid examination. Extended testing for infective and environmental exposures was facilitated by Public Health Wales. Results: All cases are male, aged 25–75. All except one had a preceding prodromal viral illness. Three cases had prominent and early facial biplegia, which presented asymmetrically resulting in ITU support and nasogastric feeding. One of these had minimal motor involvement in his distal upper-limbs, one developed a more typical GBS picture and the third developed a complete ophthalmoplegia without ataxia. A fourth case had asymmetric lower limb weakness and a fifth had distal upper-limb dominant weakness. Nerve conduction studies were in keeping with AMAN in two. Conclusions: These cases are remarkable as they are from a distinct temporal and geographic area. None of these patients were positive for Campylobacter; only one has a positive anti GQ1b titre. None met the Brighton criteria for classic GBS or Miller Fisher syndrome. This cluster is currently the focus of an investigation by Public Health Wales.